Knowledge management in communites of practice: the Backyard Mechanics “Gereji Bubu” of Dar es Salaam - Mwasubila, Jofrey Amanyisye (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.